DIGITAL LITERACY AND AI UTILIZATION IMPACTS ON ENGLISH WRITING PROFICIENCY IN INDONESIAN HIGHER EDUCATION - Swari, Utami Ratna; Masluha, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid integration of artificial intelligence in education has transformed how Indonesian university students approach academic writing. This study investigates the influence of digital literacy and the utilization of artificial intelligence on English writing proficiency. Using a quantitative explanatory survey design, data were collected from fifty-five undergraduate students selected through purposive sampling at a private university. The study employed a structured questionnaire to measure information evaluation, ethical awareness, and artificial intelligence usage patterns. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares. The results demonstrate that digital literacy significantly enhances writing proficiency by enabling students to evaluate sources and maintain ethical standards. Similarly, the utilization of artificial intelligence positively impacts writing outcomes, particularly in improving grammatical accuracy and lexical sophistication. Furthermore, the simultaneous interaction of these variables serves as a strong predictor of overall writing competence. The findings conclude that while artificial intelligence provides essential technical support, digital literacy remains the critical cognitive foundation for effective usage. These insights suggest that higher education institutions should prioritize integrated curriculums that combine technical training with robust digital literacy education to foster independent and proficient academic writers.